Implementasi KTSP dalam Pembelajaran IPA SMP - Sumiyati -- (Jurnal Pendidikan dan Kebudayaan, 2010)
This research was aimed at describing teachers opinion about the implementation of the program comprises planning, activities in the classroom, and the report of Science Teaching-Learning of School-Based Curriculum implementation and its factors affecting it. There are 40 respondents from 11 State and Private Junior High Schools in Bekasi District. The instruments consist of questionnaires in the form of Liker Scale. The data is then analyzed using descriptive analyses in tables distributing frequency and percentage for each indicator and each dimension of School-Based Curriculum Implementation. The data shows that (1) The planning of the program: writing syllabus; lesson plan, and remedial/enrichment indicate that most respondents are at moderate level, others are at low level and the others are at very low level. (2) The implementation of the program including syllabus, lesson plan components and remedial/enrichment indicate most respondents are at moderate level while the remaining are at the very low level., and (3) The report consisting of process and outcome evaluations, indicate that only a few respondents are at moderate level, and most of them are at the level of very low.